2019
DOI: 10.3390/ma12182895
|View full text |Cite
|
Sign up to set email alerts
|

TiO2–SrTiO3 Biphase Nanoceramics as Advanced Thermoelectric Materials

Abstract: The review embraces a number of research papers concerning the fabrication of oxide thermoelectric systems, with TiO2−SrTiO3 biphase ceramics being emphasized. The ceramics is particularly known for a two-dimensional electron gas (2DEG) forming spontaneously on the TiO2/SrTiO3 heterointerface (modulation doping), unlike ordinary 2DEG occurrence on specially fabricated thin film. Such effect is provided by the SrTiO3 conduction band edge being 0.40 and 0.20 eV higher than that for anatase and rutile TiO2, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 172 publications
(308 reference statements)
0
4
0
Order By: Relevance
“…[78] But compared with those advanced thermoelectrics (e.g., Bi 2 Te 3 , SnSe), more efforts should be devoted to further improve thermoelectric performance of oxide perovskites (e.g., strategies to decrease thermal conductivity), which have been comprehensively prospected in some reviews. [79,80] For the halide perovskites, the attracting characteristics lie in their high Seebeck coefficient and excellent carrier mobility, but exploration regarding its thermoelectric behaviors has only begun recently, mainly focusing on theoretical analysis and prediction of thermoelectric performance. [81] In 2016, Mattoni et al demonstrated a theoretical calculation of thermoelectric properties of MAPbI 3 and predicted that it could deliver a ZT value of 1-3 at room temperature via electron doping strategy.…”
Section: Thermoelectric Effectmentioning
confidence: 99%
“…[78] But compared with those advanced thermoelectrics (e.g., Bi 2 Te 3 , SnSe), more efforts should be devoted to further improve thermoelectric performance of oxide perovskites (e.g., strategies to decrease thermal conductivity), which have been comprehensively prospected in some reviews. [79,80] For the halide perovskites, the attracting characteristics lie in their high Seebeck coefficient and excellent carrier mobility, but exploration regarding its thermoelectric behaviors has only begun recently, mainly focusing on theoretical analysis and prediction of thermoelectric performance. [81] In 2016, Mattoni et al demonstrated a theoretical calculation of thermoelectric properties of MAPbI 3 and predicted that it could deliver a ZT value of 1-3 at room temperature via electron doping strategy.…”
Section: Thermoelectric Effectmentioning
confidence: 99%
“…134 These superlattices remarkably reduces the κ of the materials and enhanced the ZT values. 135 First time, idea of superlattice was given by Venkatasubramanian 136 to improve the value of ZT by reducing the κ l . Further this approaches continuously explored by other researchers.…”
Section: Superlatticesmentioning
confidence: 99%
“…Based on the simulated electronic structures, the thermoelectric transport properties of n-type BiCuOCh are calculated by the semiclassical Boltzmann theory via the BoltzTraP package [32,33]. Similar to treatments employed in literature [13], constant relaxation time approximation is used in the calculations of thermoelectric transport properties, because the scattering time of most semiconductors is insensitive to energy [34]. A Monkhost-Pack mesh of 31 × 31 × 13 k-point is used to obtain the accurate thermoelectric transport properties of BiCuOCh [35,36].…”
Section: Computational Detailsmentioning
confidence: 99%
“…Materials 2020, 13, x FOR PEER REVIEW 3 of 13 semiconductors is insensitive to energy [34]. A Monkhost-Pack mesh of 31 × 31 × 13 k-point is used to obtain the accurate thermoelectric transport properties of BiCuOCh [35,36].…”
Section: Crystal Structuresmentioning
confidence: 99%